Subjective Questions to Measure Welfare and Well-being - Ada Ferrer-i-Carbonell (Tinbergen Institute, 2002)
This paper provides arguments in favor of using subjective questions as a proxy to measure welfare and well-being. This approach makes it possible to avoid having to define welfare and well-being means and having to identify the relevant indicators. Instead, individuals themselves define their level of welfare and well-being. For a meaningful analysis of subjective questions, two main assumptions are needed: namely, that individuals are able to evaluate their own situation, and that responses among individuals can be compared. Both assumptions are discussed here. Next, empirical studies that use subjective questions are surveyed. This offers a fIrst approximation of the structure of individual well-being and preferences. Finally, four areas of application are identified, along with a short survey of relevant studies.
Keywords: D6; I30; I31; 330; Preferences; Satisfaction; Welfare measurement; Well-being measurement; Lebensqualität; Wohlfahrtsanalyse; Messung